Financial and economic aspects of urban vegetable farming - Danso, George K.; Hope, L.; Drechsel, Pay (2014)
This chapter explores some of the financial and economic aspects of urban and peri-urban agriculture in Ghana. Cost-benefit analysis comparisons were made of farm finances of common rural, peri-urban and urban farming systems. Substudies also tried to quantify benefits for society and to cost externalities related to soil nutrient depletion, pesticide use and urban malaria.